2001
DOI: 10.1002/1097-4636(20010905)56:3<406::aid-jbm1110>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Chain-length dependence of the protein and cell resistance of oligo(ethylene glycol)-terminated self-assembled monolayers on gold

Abstract: Oligo(ethylene glycol) (O-EG(n))-terminated alkanethiol surface-assembled monolayers (SAMs) have been reported to demonstrate protein-resistant properties similar to those of poly(ethylene glycol) (PEG). In this study, we compared the relative protein resistance of short and long ethylene oxide chains, SAMs of PEG 5000, PEG 2000, O-EG(3) (molecular weight = 120), and O-EG(6) (molecular weight = 240), on gold surfaces. Surface plasmon resonance showed that these monolayers were all protein-resistant within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
147
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(175 citation statements)
references
References 49 publications
23
147
5
Order By: Relevance
“…The cleaned chip surface is hydrophilic, with a contact angle of 16°-22°. Following the coating process, the PEG and PEOU surfaces exhibited contact angles of 42°-46°and 48°-56°, respectively (not shown here), revealing results similar to those reported elsewhere (Lee and Laibinis 1998;Zhu et al 2001). The same terminal groups (OH for both PEG and PEOU) are associated with similar contact angles.…”
Section: Observation Of Water Contact Anglesupporting
confidence: 89%
“…The cleaned chip surface is hydrophilic, with a contact angle of 16°-22°. Following the coating process, the PEG and PEOU surfaces exhibited contact angles of 42°-46°and 48°-56°, respectively (not shown here), revealing results similar to those reported elsewhere (Lee and Laibinis 1998;Zhu et al 2001). The same terminal groups (OH for both PEG and PEOU) are associated with similar contact angles.…”
Section: Observation Of Water Contact Anglesupporting
confidence: 89%
“…PEG has been shown to be able to form a stealth corona around liposomes, significantly reducing the rapid uptake of intravenously injected particulate drug carriers by cells of the mononuclear phagocyte system (MPS) [132,133]. It has been demonstrated theoretically [134][135][136][137] and experimentally [138][139][140][141][142][143] that protein repellence of PEG coatings depends on both chain length and chain density, which jointly determine the thickness of the adlayer [127].…”
Section: Agents For the Stabilization Of Cubosomesmentioning
confidence: 99%
“…These studies showed that proteins are reversibly adsorbed; they are removed upon rinsing the substrate with water. 120 107 Since FN mediates cell adhesion to surfaces, quantifying the amount of FN on the surface and determining conditions under which this can be controlled provides a method to tailor the amount of cell adhesion to the surface. After incubation of mixed-alkanethiol SAMs on gold substrates in radiolabeled FN for 1 h the substrates were incubated in solutions of either phosphate buffered saline ͑PBS͒ or 10% newborn calf serum in Dulbecco's modified eagle's medium for 1 or 16 h, and the amount of FN on the surface was quantified.…”
Section: 104mentioning
confidence: 99%